Effect of octenyl succinylated waxy starch as a fat mimetic on texture, microstructure and physicochemical properties of Minas fresh cheese - Diamantino, Vivian Ribeiro [UNESP]; Beraldo, Fernanda Arantes [UNESP]; Sunakozawa, Tassila Nakata [UNESP]; Barretto Penna, Ana Lucia [UNESP] (Elsevier B.V., 2014)
The effect of fat reduction and the addition of octenyl succinylated (OS) waxy maize starch as a fat replacer on the physicochemical properties, texture, and microstructure of Minas fresh cheese was studied. The cheeses were produced according to three formulations: full-fat cheese (FC), reduced-fat cheese (RC), and reduced-fat cheese with 0.5 kg/100 L of added starch (SC). Analyses of the chemical composition, titratable acidity, water-holding capacity (WHC), yield, texture, microstructure, and electrophoretic profile of casein were conducted. Fat reduction increased the hardness and decreased the yield of the cheeses. Fat reduction also promoted a denser microstructure and less proteolysis. The concentration of starch that was added was insufficient to improve the yield and texture parameters of the reduced-fat cheese. However, the addition of starch increased the moisture content and the WHC of the reduced-fat cheese. In general, OS waxy maize starch improved the overall quality of the reduced-fat Minas fresh cheese. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reduced-fat cheese; Fat replacer; Scanning electron microscopy; Texture profile analysis; Electrophoretic profile of casein